La réforme régionale en France : une occasion manquée ? - Élisabeth Bonnet-Pineau (EchoGéo)
In 2014 the new administrative map of France reduced the number of regions from 22 to 13. The emergence of the region as a territorial collectivity with specific responsibilities was slow and only became operational in 1982. In recent years, several reports have proposed a reduction in the number of regions and a redefinition of the responsibilities of departmental councils and of regional councils. The main objective of the reform sought to ‘give the regions a critical size’ to enable them ‘to exercise the strategic responsibilities attributed to them and to achieve efficiency gains’. Alongside the regions, the departmental councils are inscribed into the institutional landscape, together with larger and larger intercommunal units (intercommunalités). The objective of making savings could only be achieved by reinforcing intercommunal units, and hence governmental responsibilities of other territorial collectivities have been planed down. Preference has been given to mergers, but the issue of scale has not been applied evenly. The reform appears to be a missed opportunity.